PEMIKIRAN AGAMA DAN NEGARA MOHAMMAD NATSIR - Rizky Aulia; Retanisa Rizqi (Siyasah Jurnal Hukum Tatanegara, 2022)
Mohammad Natsir is an intellectual figure who is well-known as one of the figures who voiced that Islam can be used as the basis of the state. Mohammad Natsir tried to unite Islam and the State in Indonesia. The purpose of this study is to examine the thoughts of Mohammad Natsir about the relationship between Islam and the state, using the library search method. The relationship between Islam and the State in Mohammad Natsir's view is an integrated relationship between politics, economics and a way of life that does not recognize the separation between religion and politics. Mohammad Natsir said that the state is not the ultimate goal of Islam but it is to become a tool in implementing Islamic rules contained in the Qur'an and Sunnah.